1984
DOI: 10.1002/jcb.240240404
|View full text |Cite
|
Sign up to set email alerts
|

Secretion and degradation of mutant leucine‐specific binding protein molecules containing C‐terminal deletions

Abstract: The leucine-specific binding protein (LS-BP), a periplasmic component of the Escherichia coli high-affinity leucine transport system, is initially synthesized in a precursor form with a 23 amino acid N-terminal leader sequence that is removed during secretion of the protein into the periplasm. Using in vitro mutagenesis, deletion mutants of the LS-BP gene have been constructed with altered or missing amino acid sequences in the C-terminal portion of the protein. These altered binding proteins exhibited normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Proteolytic events in this compartment of the cell include processing of signal sequences for exported proteins and turnover of abnormal proteins (4,11,14). Much less evidence is available for turnover of native functional proteins.…”
mentioning
confidence: 99%
“…Proteolytic events in this compartment of the cell include processing of signal sequences for exported proteins and turnover of abnormal proteins (4,11,14). Much less evidence is available for turnover of native functional proteins.…”
mentioning
confidence: 99%
“…In this model, a major role of the membrane potential is suggested for the proper membrane orientation of the proposed helix hairpin formed by the signal sequence and the first segment of the mature portion of the BP [ 16,171, Recent work on the secretion of the BPs has been directed toward identifying the sequences required to achieve secretion. To this end, mutants of LS-BP carrying various deletions or sequence alterations have been constructed [17]. It was found that these altered binding proteins were processed and secreted normally.…”
Section: Secretion Of the Bps Into The Periplasmmentioning
confidence: 99%
“….The first group includes pauses that occur about 8-12 nucleotides downstream from a 'hairpin' stem-loop structure in the transcript. The best-studied example is in the frp attenuator region, rrpt [7]. Recent evidence suggests that DNA sequences downstream of the trpL pause site also determine pause half-life [10,12].…”
Section: Introductionmentioning
confidence: 99%